Skin Cell Phototoxicity and Photoprotection Study of Agro-Derived Lignin and Nanocellulose - Cruz, Juliana Varella; Maddaleno, Adriana Solange; Gava, Julia Salles; Magalhães, Washington Luiz Esteves; de Oliveira, Danielle Palma; Leme, Daniela Morais; Mitjans, Montserrat; Vinardell, Maria Pilar (MDPI, 2025)
Lignin, a significant industrial byproduct from paper manufacturing processes, exhibits ultraviolet (UV) radiation absorption properties. Cellulose nanofibers (CNFs) demonstrate universal ligand characteristics and represent an innovative approach for converting industrial waste into value-added products. Given their potential applications in cosmetic formulations, their efficacy and safety parameters, such as their photoprotection mechanisms and phototoxicity, need to be investigated. Therefore, two kraft lignin fractions, LE and R1, along with a kraft-bleached pulp CNF, were evaluated for their phototoxicity and photoprotection mechanisms, both using the HaCaT cell line (immortalized human keratinocytes) as the in vitro model. Phototoxicity assessment involved exposing cells to UVA radiation (4 J/cm2), with the subsequent comparison of cell viability between irradiated and non-irradiated samples. ROS quantification was performed using a 2′,7′-dichlorofluorescein diacetate (DCF-DA) probe, with fluorescence intensity measurements, and was then used to evaluate the photoprotection effect. The results demonstrated that both LE and R1 exhibited concentration-dependent increases in phototoxicity, whereas CNF showed no phototoxic effects under the conditions tested. For photoprotection, LE, R1, and CNF reduced UV-induced ROS production, a result which could be associated with antioxidant properties in the case of the lignin fractions. These findings suggest that both lignin fractions and CNF hold promise for use in renewable and sustainable cosmetic formulations.